2022
DOI: 10.1149/ma2022-02642301mtgabs
|View full text |Cite
|
Sign up to set email alerts
|

A Strategy to Suppress the Electrochemo-Mechanical Degradation in Solvent-Free Electrodes for All-Solid-State Batteries

Abstract: In response to the safety concerns on highly flammable liquid electrolytes in lithium-ion batteries (LIBs), the all-solid-state batteries (ASSBs) have emerged as promising alternatives for the next generation. The use of solid electrolytes with low flammability can provide resistance to fire/explosion incidents under abnormal conditions. In addition, it is expected that high power and high energy density can be achieved using high-voltage cathode materials due to the wide electrochemical window of solid electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Hence, PTFE stands as an optimal candidate for ASSBs. 41,42 Li et al demonstrated the utility of fibrillized PTFE in creating thin sulfide solid electrolyte films (∼40 μm, 8.5 mS cm −1 at 25 °C) and cathode films (∼60 μm) through a solvent-free technique. Incorporating these films into ASSBs resulted in an initial discharge capacity of 160 mA h g −1 at 0.1 C and 110 mA h g −1 at 1 C, exhibiting remarkable cycle longevity with capacity retentions of 91.4% and 86.4% after 100 and 1000 cycles, respectively.…”
Section: Chipping Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Hence, PTFE stands as an optimal candidate for ASSBs. 41,42 Li et al demonstrated the utility of fibrillized PTFE in creating thin sulfide solid electrolyte films (∼40 μm, 8.5 mS cm −1 at 25 °C) and cathode films (∼60 μm) through a solvent-free technique. Incorporating these films into ASSBs resulted in an initial discharge capacity of 160 mA h g −1 at 0.1 C and 110 mA h g −1 at 1 C, exhibiting remarkable cycle longevity with capacity retentions of 91.4% and 86.4% after 100 and 1000 cycles, respectively.…”
Section: Chipping Resistancementioning
confidence: 99%
“…PTFE has emerged as a highly promising material for the fabrication of all-solid-state batteries (ASSBs) due to its noninteraction with electrolytes and active materials and its electrochemical stability even under high voltage conditions. Hence, PTFE stands as an optimal candidate for ASSBs. , Li et al demonstrated the utility of fibrillized PTFE in creating thin sulfide solid electrolyte films (∼40 μm, 8.5 mS cm –1 at 25 °C) and cathode films (∼60 μm) through a solvent-free technique. Incorporating these films into ASSBs resulted in an initial discharge capacity of 160 mA h g –1 at 0.1 C and 110 mA h g –1 at 1 C, exhibiting remarkable cycle longevity with capacity retentions of 91.4% and 86.4% after 100 and 1000 cycles, respectively.…”
Section: Types Of Bindersmentioning
confidence: 99%